PEMANFAATAN LIMBAH CAIR TAHU DAN DAUN GAMAL (Gliricidia sepium) SEBAGAI PUPUK ORGANIK CAIR DENGAN METODA FERMENTASI DENGAN AKTIVATOR EM4 - Nasution, Hasmalina; J, Henny D; Laira, Ulsanna (Sistem Informasi, 2017)
Liquid organic fertilizer is organic fertilizer in a liquid preparation as apart or all of from organic compound such as plant, animal, and industry waste, solid or liquid phase Nutrients contained therein form of a solution that is so fine that is easily absorbed by plants, though the leaves or stems. Organic fertilizer is one of solution to recovery physical, chemical and biological soil mineral from harmful effect at synthetic fertilize. Liquid fertilizer is obtained from the fermentation process solid first and then proceed with the extraction and liquid anaerobic fermentation process.In the fermentation process, the role of microbes largely determine the resulting product.The aim of this study was to determine the potential of liquid waste out as a liquid organic fertilizer with the addition of leaves of Gliricidia plants with a variation of 200 gr and 400 gr to increase mocro and micro nutrients with EM4 bacteria activator by fermentation procces. Macro nutrients result show Nitrogen 1250,57 ppm, phosphorus 1626,51 ppm potasium 2987,45 ppm, C-organic 8550 ppm, the ratio of C/N 7, and micro nutrients (Fe, Cu, Mn) C organic result Fe 57.99 ppm, Cu 0.30 ppm, Mn 2.83 ppm in the optimum fermentation time of 5 days with additional variations Gliricidia leaves 400 g. Macro nutrient of Organic fertilizer produced meets the quality requirements of the regulation which has set the levels of nitrogen, phosphorus and potassium in the amount of <2% or <20000, C organic â¥ 4% (40000 ppm), the ratio of C / N â¥ 4 ppm. Micro nutrients result do not meet the quality requirements of the agriculture minister No.28/Permentan/OT.140/2/2009. quality regulations for, and metal 100-1000 ppm.